A Dynamic Perspective on Diverse Teams: Moving from the Dual-Process Model to a Dynamic Coordination-based Model of Diverse Team Performance. Issue 1 (1st January 2016) - Srikanth, Kannan; Harvey, Sarah; Peterson, Randall
Abstract: The existing literature on diverse teams suggests that diversity is both helpful to teams in making more information available and encouraging creativity and damaging to teams in reducing cohesion and information sharing. Thus the extant literature suggests that diversity within teams is a double-edged sword that leads to both positive and negative effects simultaneously. This literature has not, however, fully embraced the increasing calls in the broader groups literature to take account of time in understanding how groups function [e.g. Cronin, M. A., Weingart, L. R., & Todorova, G. (2011). Dynamics in groups: Are we there yet? The Academy of Management Annals, 5, 571–612]. We review the literature on diverse teams employing this lens to develop a dynamic perspective that takes account of the timing and flow of diversity's effects. Our review suggests that diversity in groups has different short-term and long-term effects in ways that are not fully captured by the currently dominant double-edged sword metaphor. We identify an emerging perspective that suggests a tropical depression metaphor—that has the potential, over time, to develop either into a dangerous hurricane or diffuse into a rainstorm that gives way to sunshine, as more apt to capture the dynamic effects of diversity in teams. We conclude by outlining an agenda for redirecting future research on diverse teams using this more dynamic perspective.